An evolutionary conserved interaction between the Gcm transcription factor and the SF1 nuclear receptor in the female reproductive system. - Cattenoz, P.B.; Delaporte, C.; Bazzi, W.; Giangrande, A. (Scientific reports, 2016)
NR5A1 is essential for the development and for the function of steroid producing glands of the reproductive system. Moreover, its misregulation is associated with endometriosis, which is the first cause of infertility in women. Hr39, the Drosophila ortholog of NR5A1, is expressed and required in the secretory cells of the spermatheca, the female exocrine gland that ensures fertility by secreting substances that attract and capacitate the spermatozoids. We here identify a direct regulator of Hr39 in the spermatheca: the Gcm transcription factor. Furthermore, lack of Gcm prevents the production of the secretory cells and leads to female sterility in Drosophila. Hr39 regulation by Gcm seems conserved in mammals and involves the modification of the DNA methylation profile of mNr5a1. This study identifies a new molecular pathway in female reproductive system development and suggests a role for hGCM in the progression of reproductive tract diseases in humans.